2015
DOI: 10.1021/acs.nanolett.5b00614
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Nanocrystals

Abstract: Abstract:We demonstrate the facile synthesis of high purity aluminum nanocrystals over a range of controlled sizes from 70 nm to 220 nm diameter, with size control achieved through a simple modification of solvent ratios in the reaction solution. The monodisperse, icosahedral and trigonal bipyramidal nanocrystals are air-stable for weeks, due to the formation of a 2-4 nm thick passivating oxide layer on their surfaces. We show that the nanocrystals support sizedependent ultraviolet and visible plasmon modes, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
245
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(250 citation statements)
references
References 28 publications
4
245
0
1
Order By: Relevance
“…In the plotted snapshot, formation of the hotspots at the offset spots between nanodisks is clearly visible. The full optical responses of simple and complex aluminum antennas such as scattering profiles, and extinction spectra are discussed with details in previous studies [28,53], hence, here we just considered the absorption properties of the proposed heptamer assemblies. Since the oxidation of aluminum in the subwavelength regime also affects the dielectric permittivity of the particles, the thickness of the oxide layer has an important role in hybridization of plasmon resonances in closely spaced nanoparticle assemblies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the plotted snapshot, formation of the hotspots at the offset spots between nanodisks is clearly visible. The full optical responses of simple and complex aluminum antennas such as scattering profiles, and extinction spectra are discussed with details in previous studies [28,53], hence, here we just considered the absorption properties of the proposed heptamer assemblies. Since the oxidation of aluminum in the subwavelength regime also affects the dielectric permittivity of the particles, the thickness of the oxide layer has an important role in hybridization of plasmon resonances in closely spaced nanoparticle assemblies.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of oxide layer on the scattering efficiency profile for an isolated nanodisk with an oxide thickness of t ox~2 -3 nm have been examined, theoretically and experimentally [18]. Besides, it is shown that increasing the thickness of the oxide layer results in a red-shift of scattering dipolar resonance peak to the longer wavelengths (from UV to the visible band) [53]. This red-shift also contains dramatic decrements in the scattering efficiency peak.…”
Section: Resultsmentioning
confidence: 99%
“…The above results and discussions show that the diffusion of molecules in solvent plays an important role in the structure evolution of assemblies, which puts forward a different research line in considering the effect of solvents on the structure of materials. Various hierarchical structures of materials were synthesized by regulating solvents [30][31][32]. But our understanding on why and how the solvents play their role in shaping these structures is limited.…”
Section: Resultsmentioning
confidence: 99%
“…These metals include among others Rh, Ru or Pd, which have already been used in heterogeneous catalysis. Although Al by itself is a poor catalytic metal, it has been demonstrated that Al nanocrystals can also act as photocatalysts for hydrogen dissociation [39]. Densely distributed Al NPs have been also used to assist photocatalytic processes [40,41].…”
Section: Aluminummentioning
confidence: 99%